Unia Europejska na łamach drukowanej prasy lokalnej - Jurga-Wosik, Ewa (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2008)
The first publications concerning the European Union appeared in the local press in the early 1990s. These messages were concealed, i.e. they did not provide direct information about the functioning of the EU. The political campaign to saturate local press with EU news commenced when Polish cities and towns commonly began to declare collaboration with the cities and towns in EU member states (‘partner cities’ or ‘twin towns’). Direct announcements concerning the EU appeared in the late 1990s. The significance of this information was growing (that is a quantitative and qualitative increase of such releases in the press) as the negotiations on Poland’s accession to the EU progressed.
The European Union in the Local Printed Press